Violation of human rights and The Jurisdiction of The International Criminal Court - Likadja, Jeffry Alexander Ch; Saudila, Novilinda Dwiputri Irtanti (Dynamics of Politics and Democracy, 2023)
Purpose: Territorial disputes remain a crucial issue within the doctrine of national sovereignty, despite international law promoting borderless cooperation. In reality, such conflicts, like the one between Palestine and Israel, continue and result in significant casualties and humanitarian crises. This study aims to analyze humanitarian crimes in the Palestine-Israel conflict zone and assess the jurisdiction of the International Criminal Court (ICC) in addressing them. Methodology: The research uses a normative legal approach based on international regulations and case studies. It relies on secondary legal sources through library research and qualitative descriptive analysis. Results: The findings indicate severe human rights violations, particularly against civilians, including women and children, and damage to non-military facilities. These acts reflect violations of humanitarian law and fall under the ICC’s jurisdiction, which includes genocide, crimes against humanity, war crimes, and aggression. Conclusion: The ICC, although limited in its reach over non-party states, remains a crucial body for pursuing justice and accountability in international humanitarian crises when national systems fail to act. Limitations: The study is confined to the humanitarian aspects of the Israel-Palestine conflict without addressing territorial status or sovereignty issues. It also affirms the ICC’s jurisdiction and the UN Security Council’s obligation to act under the principle of Obligation Erga Omnes. Contribution: This research reinforces the role and limitations of the ICC in addressing gross human rights violations and underscores the need to strengthen global legal frameworks to ensure accountability beyond state sovereignty.